Parabolic convergence regions of branched continued fractions of the special form - Bodnar, D.I.; Bilanyk, I.B. (Carpathian Mathematical Publications, 2021)
Using the criterion of convergence of branched continued fractions of the special form with positive elements, effective sufficient criteria of convergence for these fractions are established. To study the parabolic regions of convergence, the element regions and value regions technique was used. In particular, half-planes are considered as value regions. A multidimensional analogue of Tron's twin convergence regions for branched continued fractions of the special form is established. The obtained results made it possible to establish the conditions for the convergence of the multidimensional S-fractions with independent variables.